ARCHITECTURAL GRAPHICS AND COLOR: INTERACTION IN THE VISUALIZATION OF IDEAS - Собко, Юлія; Овсієнко, Ольга; Рєзанова, Катерина (SWorldJournal, 2025)
The article explores the role of architectural graphics and color as complementary tools in the visualization of architectural ideas. It emphasizes the significance of graphical language as a medium of communication between architects and society, while h